ANALISIS PENGGUNAAN MODAL KERJA PADA KOPERASI PRODUSEN SATAHI DI SORKAM - Bella Juena Dewi; Safriadi Pohan; Rifka Hadia Lubis (CV. ALIM'SPUBLISHING, 2023)
This study aims to analyze and calculate the ratio of liquidity, calculate the ratio of activities using working capital to earn profit (profitability ratio) and see the effectiveness of using working capital compared to a predetermined standard of measurement. The type of research used is case study research with a quantitative approach. The processed data includes the financial reports of the Satahi Sorkam Producers Cooperative. In analyzing research data using descriptive analysis method with analysis of liquidity ratios, activity ratios and profitability ratios. Based on the results of the analysis of the liquidity ratio, the results of calculating the current ratio for 2019-2021 are obtained. In 2019 it was good, while in 2020 and 2021 it was quite good. The results of calculating the quick ratio for 2019-2021 when compared to standard measurements, the quick ratio for the 2019-2021 period is not good. Based on the activity ratio analysis, it shows that receivables turnover in 2019-2021 when compared to measurement standards, receivables turnover in 2019-2021 is less efficient. As for inventory turnover in 2019-2021 when compared to the standard, inventory turnover in 2019-2021 is less efficient. Based on the analysis of working capital turnover calculations, the results of working capital turnover in 2019-2021 are quite efficient. As for the results of the analysis and calculation of the profitability of own capital in 2019-2021 compared to measurement standards, the profitability of own capital in 2019-2021 is very efficient.